PENGARUH PERESEPAN ELEKTRONIK TERHADAP MUTU LAYANAN FARMASI DI RUMAH SAKIT “X” JAKARTA BARAT - Lily Widjaya (Lembaga Penerbitan Universitas Esa Unggul, 2013)
AbstractIndonesia through the Ministry of Health has begun implementing Hospital Information System based computer, although it is still growing rapidly but gradually it will be done in several hospitals. One application of Hospital Information Systems including electronic prescription (e - prescription) where the doctor wrote a prescription through the data entry process is automated using software that connects at the hospital pharmacy. Hospital